1985
DOI: 10.1021/bi00329a033
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin S synthetase. Temperature dependence and thermodynamic parameters of substrate amino acid activation reactions

Abstract: In the biosynthesis of the cyclic decapeptide antibiotic gramicidin S, the constituent amino acids are activated by a two-step mechanism involving aminoacyl adenylate and thio ester formation which are both reversible processes. The dissociation constants (KD) for the gramicidin S synthetase-substrate amino acid-thio ester complexes are 100-1000-fold lower compared to the KM data of the preceding aminoacyl adenylate reactions. The affinity for these substrates is appreciably higher at the thio template sites t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
(12 reference statements)
1
10
2
Order By: Relevance
“…The specific activities of both enzymes range over 20 -35 nmol gramicidin S min-' (mg protein)-'. These data are 3-4-fold higher than those reported in [7].…”
Section: Assays For Product Formationcontrasting
confidence: 60%
See 2 more Smart Citations
“…The specific activities of both enzymes range over 20 -35 nmol gramicidin S min-' (mg protein)-'. These data are 3-4-fold higher than those reported in [7].…”
Section: Assays For Product Formationcontrasting
confidence: 60%
“…Both components of gramicidin S synthetase were purified as published previously [7]. This procedure was improved efficiently by the introduction of a fast protein liquid chromatography technique (Fig.…”
Section: Enzyme Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gardner & Troy [6] suggested the occurrence of an extremely unstable PGA synthetase complex in B. licheniformis ATCC9945a. Their proposed reaction mechanism [34] was similar to those of multienzyme systems [35], such as the gramicidin S synthetase complex, which were accompanied by the cleavage of ATP into AMP. It is important for the elucidation of the mechanism of PGA synthesis by the PgsBCA system to know whether ADP or AMP is formed by the ATPase reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that thioacylation of peptide synthetases must be faster than hydrolysis, or that it regulates the conformational transition, leading to a faster transfer [18]. The affinity for the substrate amino acid is much higher at the thio template than in the adenylation centres ; consequently the activation equilibria are quantitatively shifted towards thioester formation [36,37]. The significance of a putative editing mechanism involving the thiolation site remains to be investigated further using the respective holo-enzymes.…”
Section: Discussionmentioning
confidence: 99%